A Pragmatic Analysis of Speech Acts in Wilujengan Ceremonies at Pura Mangkunegaran Palace - Ravikha Najmila Fajry; Malikatul Laila (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study investigates the pragmatic functions of speech acts used in wilujengan ceremonies at Mangkunegaran Palace, Focusing on the dominance of directive speech acts. The wilujengan ceremony, a traditional Javanese ritual of gratitude and spritual harmony, uses specific linguistic forms that reflect the cultural and religiuos beliefs of the Javanese people.Methodology: This study uses a descriptive qualitative method through technique of interviews to two courtiers and three tour guides. This study analyzes the utterances produced by the courtiers and ritual leaders during the ceremony to identify how directive speech acts such as requests, prayers, and supplications function in the ritual context.Results: The findings show that directive speech acts are the most frequently used and most meaningful type of speech act, reflecting the participants' intention to seek blessings, protection, and forgiveness from God.Applications/Originality/Value: These speech acts not only convey requests but also symbolize humility, respect, and devotion to God. This study concludes that language in wilujengan ceremonies functions as a pragmatic and spiritual instrument that bridges the human and divine worlds, illustrating the deep connection between language, culture, and spirituality in Javanese tradition.